Pharmacokinetics, efficacy and safety profiles of etanercept monotherapy in Japanese patients with rheumatoid arthritis: review of seven clinical trials. Issue 2 (March 2015) - Takeuchi, Tsutomu; Miyasaka, Nobuyuki; Kawai, Shinichi; Sugiyama, Naonobu; Yuasa, Hirotoshi; Yamashita, Noriaki; Sugiyama, Noriko; Wagerle, Lorin Craig; Vlahos, Bonnie; Wajdula, Joseph
Abstract Conventional synthetic disease-modifying anti-rheumatic drugs, including methotrexate, may not be tolerated by all patients with rheumatoid arthritis (RA), and limited international data for etanercept (ETN) monotherapy are available. The aim of this review was to summarize the clinical program for ETN monotherapy in Japanese patients with RA, which has included a pharmacokinetic study, clinical trials for registration, long-term studies, and once-weekly dosing studies. Pharmacokinetic results showed that serum concentrations of ETN were linear with dose levels and were similar to other international studies. Across interventional studies, 652 Japanese patients with active RA were treated with ETN. In the registration studies, ETN treatment led to consistent improvement in American College of Rheumatology 20/50/70 scores, European League Against Rheumatism Good Response, Disease Activity Score 28 erythrocyte sedimentation rate remission, and Health Assessment Questionnaire disability index. In the long-term studies, efficacy was maintained for up to 180 weeks. Similar results were seen in the once-weekly studies. Across the studies, more than 870 patient-years of exposure to ETN were recorded. Discontinuations owing to lack of efficacy or adverse events were modest and no new safety signals were recorded. These studies demonstrated that ETN monotherapy is efficacious and well-tolerated in Japanese patients with RA.